KONSEP TEOLOGIS DALAM NASKAH CATOR MI’RÃJ “Menakar Islam dan Budaya Nusantara di Madura” - Ibnurrahman, Junaidi (Universitas Islam Negeri Raden Intan Lampung, 2015)
THE CONCEPT OF THEOLOGY IN MANUSCRIPT BY CATOR MI’RÃJ. “Measuring the Moslem and the Culture in Madura”: The manuscript by Cator Mi’rãj is the classic songs islam Madura. And it was originally in use by the all Wali, where the trustees at that time preaching and introduced Islam through cultures and among them was a song-macapat. Sunan Bonang, Sunan Kalijaga, Sunan Giri and Sunan Kudus, and Sunan Muria are the creators the beginning of the song-macapat. This study uses the library research. By taking many factors such as the extent of the discussion, the limited time and ability, the author will limit the objects of the research and the study of theological elements that contained in the manuscript Cator Mi’raj. What value can be retrieved from the text from Cator Mi’raj and the theological concepts in the text of the Mi’raj Cator? Based on the methods that have been used, the concepts of God in the manuscript of Cator Mi’raj is revealed, it is also including the Universal Theology of Human Behavior Theology, and Theology Theocentric and Theology Anthropocentric.